Sistem Pendukung Keputusan Pemilihan Sepeda Motor Menggunakan Metode WASPAS - Kusumaningtias, Dinar Esti; Diartono, Dwi Agus (LPPM UNIKA Santo Thomas, 2022)
Motorcycles are one of the most popular vehicles by many Indonesian people. Due to the large number of enthusiasts and requests from the public, many manufacturers make various types of motorcycles with different advantages ranging from storage capacity, types of designs and superior features in their products. Many factors must be considered in the selection of a motorcycle in accordance with the wishes so that making the selection of a motorcycle in accordance with the wishes becomes a difficult thing. Motorcycle attributes include: brand, model, type, price, engine capacity, transmission, braking, year of manufacture and fuel consumption. The recommended motorcycles are only for three well-known brands, namely Yamaha, Honda and Suzuki with the WASPAS method. The results of the recommendations from the selection of criteria for the Honda brand, type of scooter, automatic transmission and single disc braking with the WASPAS method are Honda Genio motorcycles with a Qi value = 0.928.